Vascularization in Ornamented Osteoderms: Physiological Implications in Ectothermy and Amphibious Lifestyle in the Crocodylomorphs?. Issue 1 (9th November 2017) - Clarac, F.; De Buffrénil, V.; Cubo, J.; Quilhac, A.
ABSTRACT: Vascularization in the core of crocodylian osteoderms, and in their superficial pits has been hypothesized to be a key feature involved in physiological thermoregulation and/or acidosis buffering during anoxia (apnea). However, up to now, there have been no quantitative data showing that the inner, or superficial, blood supply of the osteoderms is greater than that occurring in neighboring dermal tissues. We provide such data: our results clearly indicate that the vascular networks in both the osteoderms and the pits forming their superficial ornamentation are denser than in the overlying dermis. These results support previous physiological assumptions and indicate that vascularization in pseudosuchian (crocodylians and close relatives) ornamented osteoderms could be part of a broad eco‐physiological adaptation towards ectothermy and aquatic ambush predation acquired by the crocodylomorphs during their post‐Triassic evolution. Moreover, regressions demonstrate that the number of enclosed vessels is correlated with the sectional area of the cavities housing them (superficial pits and inner cavities). These regressions can be used to infer the degree of vascularization on dry and fossilized osteoderms and thus document the evolution of the putative function of the osteoderms in the Pseudosuchia. Anat Rec, 2017. © 2017 Wiley Periodicals, Inc. Anat Rec, 301:175–183, 2018. © 2017 Wiley Periodicals, Inc.